Modeling of CO2 solubility in pyridinium-based ionic liquids using UNIQUAC - Yunus, N.M. (American Institute of Physics Inc., 2016)
Reliable predictive methods for estimating experimental results over wide range of operating conditions are useful and highly desirable. In this paper, the solubility of CO2 in 1-butylpyridinium bis(trifluoromethylsulfonyl)imide, C4pyTf2N and 1-dodecylpyridinium bis(trifluoromethylsulfonyl)imide, C12pyTf2N ionic liquids have been measured experimentally via gravimetric method using Magnetic Suspension Balance instrument at 298.15K and in the pressures range up to approximately 30 bar. The solubility data was fitted using an activity coefficient model i.e UNIQUAC model. The interaction parameters of the model were estimated. The predicted CO2 solubility data by the model shows good agreement with the experimental data. Â© 2016 Author(s).